2022
DOI: 10.3389/fgene.2022.895247
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Three novel pathogenic ABCC2 mutations identified in two patients with Dubin–Johnson syndrome

Abstract: Background: Dubin–Johnson syndrome (DJS) is a rare autosomal recessive genetic disease which is caused by mutations in the ABCC2 gene; it is characterized by chronic hyperbilirubinemia. Here, we report two pedigrees affected with DJS which were caused by three novel pathogenic ABCC2 mutations.Case summary: The two patients exhibited intermittent low-grade, predominantly conjugated hyperbilirubinemia and showed no other abnormalities. They were diagnosed clinically with DJS. Three novel pathogenic ABCC2 mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Recent studies have confirmed that the ABCC2 gene mutation is responsible for the loss of MRP2 function, which causes DJS in affected patients. [1][2][3]5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have confirmed that the ABCC2 gene mutation is responsible for the loss of MRP2 function, which causes DJS in affected patients. [1][2][3]5].…”
Section: Discussionmentioning
confidence: 99%
“…Dubin-Johnson syndrome (DJS) is an autosomal recessive inherited disorder that causes high levels of conjugated bilirubin and changes the way the body processes coproporphyrins, leading to increased urinary excretion of coproporphyrin I relative to coproporphyrin III. DJS is caused by a mutation in the ATP Binding Cassette Subfamily C Member 2 (ABCC2) gene, which codes for the multi-drug resistance protein 2 (MRP2) bilirubin transporter and is primarily present in the canalicular membrane of hepatocytes [ 1 , 2 ]. In 1954, Dubin and Johnson documented 12 cases of persistent idiopathic jaundice with an unidentified pigment in the liver as a new clinical and pathological entity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Zhao et al, two patients diagnosed with DJS were studied. Whole-exome sequencing was conducted, and three variants (c.2980delA, c.1834C > T, and c.4465_4473delinsGGCCCACAG) were identified [11]. In a case report by Kamal et al, molecular testing for the ABCC2 gene using quantitative polymerase chain reaction was used for diagnosis, and c.2273G > T, pG785V in exon 18 was identified [12].…”
Section: Discussionmentioning
confidence: 99%
“…[4,5] At the heart of DJS is the AR inheritance of mutations in the ABCC2 gene, a key player in the transport of bilirubin and other organic anions from the liver into bile. [6,7] The authors have no funding and conflicts of interest to disclose.…”
Section: Introductionmentioning
confidence: 99%